Sodno varstvo, posegi v prostor in Aarhuška konvencija - Koritnik, Boštjan (Javna uprava, 2023)
The article presents a doctoral thesis examining the impact and significance of Article 9 of the Aarhus Convention, despite its brevity, on the foundational principles of Slovenian constitutional jurisprudence. The author portrays the request for a special public role as a legal enhancement of the checks-and-balances system among different authorities, addressing dwindling civil society confidence that it alone (without the public) can ensure that “the state authority will be a good or sufficient guardian of the (healthy living) environment and which emerges as a legal response to the ‘feeling’ of a democratic deficit”. This doctoral thesis marks the first comprehensive study of judicial protection against environmentally impactful decision-making in the spatial interventions, which – according to other decisions of the enforcement law – is characterised by a number of specifics.
Keywords: Aarhus Convention; Aarhuška konvencija; civil society; civilna družba; environmental law; javnost; judicial protection; okoljsko pravo; posegi v prostor; public; sodno varstvo; spatial intervention